Monitoring the quality consistency of Fufang Danshen Pills using micellar electrokinetic chromatography fingerprint coupled with prediction of antioxidant activity and chemometrics. Issue 15 (18th July 2016) - Ji, Zhengchao; Sun, Wanyang; Sun, Guoxiang; Zhang, Jin
Abstract : A fast micellar electrokinetic chromatography fingerprint method combined with quantification was developed and validated to evaluate the quality of Fufang Danshen Pills, a traditional Chinese Medicine, which has been used in the treatment of cardiovascular system diseases, in which the tetrahedron optimization method was first used to optimize the background electrolyte solution. Subsequently, the index of the fingerprint information amount of I was performed as an excellent objective indictor to investigate the experimental conditions. In addition, a systematical quantified fingerprint method was constructed for evaluating the quality consistency of 20 batches of test samples obtained from the same drug manufacturer. The fingerprint analysis combined with quantitative determination of two components showed that the quality consistency of the test samples was quite good within the same commercial brand. Furthermore, the partial least squares model analysis was used to explore the fingerprint–efficacy relationship between active components and antioxidant activity in vitro, which can be applied for the assessment of anti‐oxidant activity of Fufang Danshen pills and provide valuable medicinal information for quality control. The result illustrated that the present study provided a reliable and reasonable method for monitoring the quality consistency of Fufang Danshen pills.